Skills development in higher education and employment - Bennett, Neville; Dunne, Elisabeth ; Carr, Clive (Buckingham : Society for Research into Higher Education & Open University Press, 2000)
The study reported in this book sets out to gain enhanced understandings of skill acquisition in higher education and employment settings with the aim of informing and improving provision. The findings and analyses provide a clear conceptualization of core and generic skills, and models of good practice in their delivery, derived from initiatives by employers and staff in higher education.
1. Generic Skills in the Learning Society -- 2. A Conceptualization of Skills and Course Provision -- 3. Beliefs and Conceptions of Teachers in Higher Education -- 4. The Practices of University Teachers -- 5. Student Perceptions of Skills Development -- 6. Employer Initiatives in Higher Education -- 7. Employers' Perspectives on Skills and their Development -- 8. The Graduate Experience of Work -- 9. The Challenges of Implementing Generic Skills.
Includes bibliographical references and index.
Keywords: BUSINESS AND EDUCATION